A Database and Probabilistic Assessment Methodology for Carbon Dioxide-enhanced Oil Recovery and Associated Carbon Dioxide Retention in the United States. (July 2017) - Warwick, Peter D.; Verma, Mahendra K.; Attanasi, Emil D.; Olea, Ricardo A.; Blondes, Madalyn S.; Freeman, Philip A.; Brennan, Sean T.; Merrill, Matthew D.; Jahediesfanjani, Hossein; Roueche, Jacqueline; Lohr, Celeste D.
Abstract: The U.S. Geological Survey (USGS) has developed an assessment methodology for estimating the potential incremental technically recoverable oil resources resulting from carbon dioxide-enhanced oil recovery (CO2 -EOR) in reservoirs with appropriate depth, pressure, and oil composition. The methodology also includes a procedure for estimating the CO2 that remains in the reservoir after the CO2 -EOR process is complete. The methodology relies on a reservoir-level database that incorporates commercially available geologic and engineering data. The mathematical calculations of this assessment methodology were tested and produced realistic results for the Permian Basin Horseshoe Atoll, Upper Pennsylvanian-Wolfcampian Play (Texas, USA). The USGS plans to use the new methodology to conduct an assessment of technically recoverable hydrocarbons and associated CO2 sequestration resulting from CO2 -EOR in the United States.